Um estudo sobre a pobreza multidimensional na Região Nordeste do Brasil - Silva, Ana Márcia Rodrigues da (2009)
The poverty is very complex to be restricted to the income insufficiency. This is a multidimensional problem that if express in terms of deficiency of basic capabilities and unmet human needs. Therefore, this work has for objective to study the poverty in the Northeast region of Brazil being considered multidimensional aspects of privation. Thus, it is initiated with a brief history of poverty. Then, it present a discussion about poverty and inequality and its complexity in Latin America and Brazil, according to the predominant vision. So, it is distinguished as this question is alarming in the Northeast region. At criticize this optics on the basis of the Capabilities Theory and the Human Needs approaches to broach poverty as a multidimensional phenomenon. To make operational this phenomenon in the Brazilian Northeast context, a multiple correspondence analysis is carried out using qualitative variables selected from the National Research for Sample of Domiciles (PNAD) of the years of 1995, 1999, 2002 and 2006. Therewith, factorial scores are extracted to calculate a synthetic index of multidimensional poverty. The complexes indexes of poverty obtained are compared with unidimensional indicators. Soon after, multidimensional inequality is focused through the estimation of inequality indices esteem based on this concept. Finally, the profile of the Northeastern poverty is traced through the decompositions of the poverty. By means of the empirical analysis it was possible to conclude that when treating the poverty in an only dimension the real poverty can be evidently neglected, since the multidimensional indicators were not consonant with the unidimensional indicators in all years used in the analysis.